2006
DOI: 10.1111/j.1525-139x.2006.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

UNRESOLVED ISSUES IN DIALYSIS: Ultrapure Dialysate: Facts and Myths

Abstract: During hemodialysis, blood comes in contact with a large volume of dialysate. Since the purity of dialysate has been linked to acute and long-term complications in hemodialysis patients, the limit of bacterial and endotoxin contamination has been reduced in recent years. Questions have been raised as to whether ultrapure dialysate is required to prevent such complications; in particular, the chronic inflammatory status frequently found in chronically hemodialyzed patients. In vivo and in vitro data suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In recent years, the maximum limit of bacterial and endotoxin contamination in dialysate has been reduced. For the currently recommended ultrapure dialysate, the Association for the Advancement of Medical Instrumentation introduced a bacterial count limit of less than 0.1 CFU/ml and an endotoxin level of less than 0.03 EU/ml, which is identical to the detection limit provided by the commonly used Limulus amebocyte lysate assay [13]. The use of an ultrapure dialysate results in a reduction in dialysate endotoxin level, and is reported to reduce inflammatory responses in hemodialysis patients, such as the increase in plasma levels of C-reactive protein (CRP), interleukin-6, and β 2 -microglobulin [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the maximum limit of bacterial and endotoxin contamination in dialysate has been reduced. For the currently recommended ultrapure dialysate, the Association for the Advancement of Medical Instrumentation introduced a bacterial count limit of less than 0.1 CFU/ml and an endotoxin level of less than 0.03 EU/ml, which is identical to the detection limit provided by the commonly used Limulus amebocyte lysate assay [13]. The use of an ultrapure dialysate results in a reduction in dialysate endotoxin level, and is reported to reduce inflammatory responses in hemodialysis patients, such as the increase in plasma levels of C-reactive protein (CRP), interleukin-6, and β 2 -microglobulin [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, switching from low- to high-flux membranes with a larger pore size may increase the transfer of endotoxin and its fragments during routine high-flux HD via backfiltration, which may contribute to enhanced cytokine induction. These factors together may explain the observation of similar effects of low- and high-flux polysulphone membranes on the inflammatory mediators in our study [13]. …”
Section: Discussionmentioning
confidence: 68%
“…Although there are an increasing number of clinical studies [15,16,17,18] showing the impact of dialysate endotoxin contamination in high-flux HD on long-term HD-related complications, it is unknown which endotoxin contamination limit can minimize endotoxin exposure-related adverse effects [15,19]. Our study demonstrated that the quality of the dialysate is correlated with the levels of endotoxin contamination.…”
Section: Discussionmentioning
confidence: 69%